Protective Effect of Whole and Fat-Free Fluoridated Milk, Applied before or after Acid Challenge, against Dental Erosion - Cassiano, Luiza P.S.; Charone, Senda; Souza, Juliana G.; Leizico, Ligia C.; Pessan, Juliano P. [UNESP]; Magalhães, Ana Carolina; Buzalaf, Marília Afonso Rabelo (Karger Publishers, 2016)
This study analysed in vitro the effect of milk against dental erosion, considering three factors: the type of milk (bovine whole/fat-free), the presence of different fluoride concentrations and the time of application (before/after erosive challenge). Bovine enamel (n = 15/group) and root dentine (n = 12/group) specimens were submitted to the following treatments: after the first erosive challenge - 0.9% NaCl solution (negative control), whole milk with 0, 2.5, 5.0 and 10.0 ppm F, fat-free milk with 0, 2.5, 5.0 and 10.0 ppm F, and 0.05% NaF solution (positive control); before the first erosive challenge - whole milk with 0, 2.5, 5.0 and 10.0 ppm F, fat-free milk with 0, 2.5, 5.0 and 10.0 ppm F, and 0.05% NaF solution (positive control). Specimens were submitted to demineralisation-remineralisation regimes 4 times/day for 5 days. The response variables were enamel and dentine loss (in micrometres). Data were analysed using Kruskal-Wallis/Dunn's test (p < 0.05). For enamel, whole milk containing 10 ppm F, applied before the erosive challenge, was the most protective treatment, but with no significant difference compared with the same treatment carried out after the erosive challenge. For dentine, whole fluoridated milk (all concentrations, after), fat-free 10 ppm F milk (after, before) and whole milk with or without F (except 2.5 ppm F, all before) significantly reduced dentine erosion. It seems that the presence of fluoride, especially at 10 ppm, is the most important factor in reducing dental erosion.
Keywords: Dentine; Enamel; Fluoride; Milk; Tooth Erosion